A comparison of self-measured and researcher-measured digit ratio (2D:4D). (18th August 2019) - Richards, Gareth; James, Trevor Keith
Abstract: The largest investigation of digit ratio (2D:4D), the BBC Internet Study, reported on finger lengths measured by participants themselves, yet data validating this technique are scarce and the reliability has been questioned. The current study aimed to calculate reliability and repeatability statistics for self-measured 2D:4D and to examine the correlations with researcher-measures. One hundred and seventy-eight undergraduate psychology students attending a practical class self-measured their finger lengths with rulers; a researcher using digital Vernier calipers measured the second and fourth fingers of a random sub-sample ( n = 97). Reliability and repeatability of self-measured 2D:4D were high, as were correlations with researcher-measurements. In each case, lower values were observed for the right–left difference in 2D:4D (D[R-L] ). Self-measured L2D:4D and M2D:4D were significantly higher than the equivalent researcher measurements, suggesting that direct comparison could be problematic. Self-measurements and directly made researcher-measurements of 2D:4D are strongly correlated, though self-measured D[R-L] is unreliable.